Characterization of Blood Culture Isolates of Streptococcus dysgalactiae subsp. equisimilis Possessing Lancefield's Group A Antigen - Brandt, Claudia M. (American Society for Microbiology, 1999)
For three human blood culture isolates of beta-hemolytic streptococci with Lancefield's serogroup A antigen, phylogenetic analysis of the 16S rRNA genes confirmed biochemical identification as Streptococcus dysgalactiae subsp. equisimilis. Genes encoding M or M-like proteins, which are considered to be major virulence determinants in streptococci, were detected in all of these strains. Our data clearly demonstrate that for beta-hemolytic streptococci, the species assignment should not be based on the results of serogrouping alone.